The impact of simvastatin on pulmonary effectors of Pseudomonas aeruginosa infection. - Emma Hennessy (Public Library of Science (PLoS), 2014)
The statin family of cholesterol-lowering drugs is known to have pleiotropic properties which include anti-inflammatory and immunomodulatory effects. Statins exert their pleiotropic effects by altering expression of human immune regulators including pro-inflammatory cytokines. Previously we found that statins modulate virulence phenotypes of the human pathogen Pseudomonas aeruginosa, and sought to investigate if simvastatin could alter the host response to this organism in lung epithelial cells. Simvastatin increased the expression of the P. aeruginosa target genes KLF2, KLF6, IL-8 and CCL20. Furthermore, both simvastatin and P. aeruginosa induced alternative splicing of KLF6. The novel effect of simvastatin on wtKLF6 expression was found to be responsible for induction of the KLF6 regulated genes CCL20 and iNOS. Simvastatin also increased the adhesion of P. aeruginosa to host cells, without altering invasion or cytotoxicity. This study demonstrated that simvastatin had several novel effects on the pulmonary cellular immune response.